'Wars of Others': National Cleavages and Attitudes towards External Conflicts. Issue 6 (1st November 2020) - Tokdemir, Efe; Akcinaroglu, Seden; Ozen, H. Ege; Karakoc, Ekrem
ABSTRACT: Why do individuals sympathize with others' wars, an antecedent of the decision to become a foreign fighter? By collecting original public opinion data from Lebanon, in 2015, and Turkey in 2017, about the actors of conflict in Syria, we test the argument that an ethno-religious cleavage at home shapes the proclivity of individuals to support others' wars. Individuals may perceive a war abroad as endangering political and social balance of power at home – and hence own survival. Therefore, when transnational identities map onto a national cleavage, as in the Sunni–Shia cleavage in Lebanon, and Turk – Kurd cleavage in Turkey, individuals are more disposed to show sympathy for others' wars both to help their kin and to protect the balance of power at home. Our findings imply that efforts to end the trend toward citizens becoming foreign fighters must start at home by mending the relations between ethnic and religious groups.